QUALITY CHARACTERISTICS OF HAKAO DIM SUM SKIN FORTIFIED WITH SEAWEED FLOUR (Eucheuma cottonii) - Dian Febi Yolanda; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT This study aimed to determine the texture characteristics of hakao dim sum wrappers fortified with seaweed flour (Eucheuma cottonii). The research method used was a non-factorial Completely Randomized Design (CRD) with 4 levels of treatment, namely K0 (0% seaweed flour), K1 (60% seaweed flour) K2 (70% seaweed flour) K3 (80% seaweed flour). The test parameters were organoleptic quality analysis of appearance, flavour, taste, and texture. The results showed that dim sum hakao wrappers fortified with 80% seaweed flour (Eucheuma cottonii) (K3) had a significant effect on organoleptic quality characteristics (appearance, flavor, and texture) at the 95% confidence level. The organoleptic quality value of the best treatment was K3 (80% seaweed flour), with organoleptic value of yellowish white appearance (8.15), slightly seaweed flavour (5.45), chewy and pliable texture (7.99), while the taste had sidnificant effect on K0 treatment, namely neutral taste, without seaweed flour (7.51)Keywords: Characteristics, Eucheuma cottonii, hakao dim sum wrappers.